Antibacterial and antioxidant activities and chemical compositions of volatile oils extracted from Schisandra chinensis Baill. seeds using simultaneous distillation extraction method, and comparison with Soxhlet and microwave-assisted extraction. Issue 1 (2nd January 2014) - Teng, Hui; Lee, Won Y
Abstract: The volatile oils were isolated from dried Schisandra chinensis Baill. seeds by Soxhlet extraction (SE), microwave-assisted extraction (MAE), and simultaneous distillation extraction (SDE), and fractions were identified by gas chromatography–mass spectrometry (GC–MS) and high-performance liquid chromatography (HPLC). The essential oils were assessed for their antioxidant and antibacterial activities. GC–MS results also revealed that the major ingredients in the oil extracted by SDE were terpenoids compounds such as ylangene (15.01%), α-phellandrene (8.23%), β-himachalene (6.95%), and cuparene (6.74), and the oil extracts of MAE and SE mainly contained aromatics such as schizandrins, wuweizisu C, and gomisin A. HPLC analysis results confirmed that more schizandrin was obtained through extraction by MAE (996.64 μg/g) and SE (722.13 μg/g). SDE oil extract showed more significant antioxidant activity than MAE or SE oil. Only volatile oil from SDE showed good antibacterial activity against all tested strains.